Pengaruh Model Pembelajaran Project Based Learning dengan Vidio Animasi Terhadap Kreativitas dan Hasil Belajar Siswa di MTs N 3 Bima - Latifah, Nurul; Efendi, M. Harja; Ramlin, Ramlin; Sazali, Munawir (Alpatih Harapan Semesta, 2025)
This study aims to analyse the influence of the Project Based Learning model through the creation of animated videos on the creativity and learning outcomes of eighth-grade students at MTsN 3 Bima. This type of research uses a quasi-experimental method with a quantitative approach involving two classes: experimental and control. Data collection was conducted using creativity observation sheets and learning outcome tests that had been validated with the Correl validity test and Cronbach's Alpha reliability test. Data analysis used the Shapiro-Wilk normality prerequisite test, Levene's test for homogeneity, and hypothesis testing using the independent sample t-test with a significance level of 5%. The research results showed a significant effect of the Project Based Learning model on students' creativity and learning outcomes, evidenced by a significance value of 0.000 < 0.05 on both variables. The conclusion of the research proves that the Project Based Learning model can enhance the creativity and learning outcomes of eighth-grade students